Sufrimiento y suicidio: estudio de caso en campesinos del sur de Brasil (2015)
ABSTRACT: The aim of this study is to understand the characteristics of suicidal behavior in Sinimbu, a rural population of German origin in the State of Rio Grande do Sul, Brazil, and reflect on some relationships with social conditions and forms of social suffering in this context. Methodology: qualitative methods (observation, interviews, discussions) and quantitative (statistical suicide 1935-2013 period), in order to reconstruct a comprehensive view of the phenomenon were applied. Results: The prevalence of suicide in this population over the past fifty years; the relevance of suicide in older age groups (over 60 years) and gradual increase in adult age groups (30-59 years); the hanging as a traditional form of suicide and social experiences of suffering that produce differentiated behaviors in front of suicide. Discussion: historical permanence of suicide suggests this phenomenon as a structural element of the population and as a plausible option to certain social and personal tensions. Also, the increase in suicide rates since the 1990s coincides with the intensification of neoliberal reforms that profoundly affect the pattern of rural life, generating higher levels of social suffering, expressed (among others) in forms of self-harm with different characteristics according gender and age.